The Right to Education and Armed Conflict: When Violence Obscures Hope and Development - Paiva Goyburu, Dante Martin (2021)
This work analyzes the injuries that are configured against the fundamental right to education in the context of armed conflicts. For this, a review is made of the scope and content of the fundamental right, as well as the situation of armed conflicts in this century, where some confrontations seem perennial. As such, it has been determined that armed conflicts and the damage they commit against the educational process end up affecting the entire educational community, with students bearing the brunt. Likewise, the situation involves both passive agents and also, in the case of minors, when the latter actively intervene as “child soldiers”. Finally, the urgency of adopting more effective measures around the problem is highlighted, taking into account that in Peru, due to the conflicts in the VRAEM, the situation is present, affecting a vulnerable sector that constantly sees its integrity in risk, but they also shy away from any opportunity for advancement as their access to education is truncated. The policies to be adopted require all the support and efforts of the national and international community.